The Pengaruh Cosplay terhadap Aktualisasi Diri : Penelitian pada Cosplayer di Instagram - cahyono, agus budi; Orydika, Rafi (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2025)
Cosplay, originating from Japan, has become a popular way for individuals, including those in Indonesia, to express themselves and gain recognition, especially through Instagram. Despite its growing influence, little research explores how cosplay contributes to self-actualization. This study, based on Maslow’s Hierarchy of Needs, examines how cosplay fulfills psychological and social needs. Using a qualitative narrative approach, data was collected through online interviews and Instagram observations of cosplayers. Findings reveal that cosplay enhances self-confidence, fosters social connections, and provides validation, especially through social media. It also helps cosplayers manage stress, express creativity, and explore career opportunities. However, challenges such as negative comments and societal pressure persist. Ultimately, cosplay proves to be a powerful tool for self-actualization, though it does not always follow Maslow’s strict hierarchy of needs. Keywords: Cosplay, Cosplayer, Hierarchy Of Needs, Instagram, Self-Actualization.